Peces de ciudad . Beached - Degregori, Felipe (Ceprodep, 2007)
Verzio FF Submission A documentary about the exclusion, discrimination and social marginalization of young Andean migrant workers in the Peruvian capital, Lima. In search for work and a better life they come from the impoverished regions such as Ayacucho, Huancavelica, Huancayo, Apurimac and Cusco with high hopes but have to soon face rejection and humiliation. Urban-rural conflicts in Peru.